ANTICARCINOGENIC ACTIVITY OF RICE BRAN PHYTIC ACID AGAINST HUMAN BREAST CANCER CELL LINE (MCF-7) - Al-Fatlawi, Atheer Abbas; A. Rizvi, M. Moshahid; Ahmad, Ayaz (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Phytic acid (PA) has been reported for anti-inflammatory, antioxidant and anticancer activity. However, molecular mechanism of anticancer activity is not clear. This study investigated the anticancer activity of rice bran PA against breast cancer (MCF-7). Cytotoxicty of PA (0 to 7 mM) against MCF-7 cells was examined by MTT and LDH assays after 24 and 48 h treatment. Apoptotic activity was evaluated by expressional analysis of apoptosis-regulatory genes [i.e., p53, Bcl-2, Bax, caspase-3 and -9] by reverse transcriptase-PCR and DNA fragmentation assay. PA inhibited the growth of MCF-7 cells in a concentration dependent manner (pâ‰¤0.04). After 48 h treatment, cells viability was recorded 80.9, 71.1, 59.8, 36.6, 26.7 and 15.9% in MTT assay and 85.3, 72.6%, 62.3%, 42.1, 31.7 and 21.7% in LDH assay at concentration of 1.4, 2.2, 3.0, 3.8, 4.6, and 5.4 mM respectively. Hence, treatment of PA for 24 h, recorded viability of cells 84.6, 73.8, 61.0, 47.0, 28.8 and 17.3% in MTT assay and 87.8, 77.5%, 62.9%, 49.8, 35.7 and 23.3% in LDH assay at concentration of 2, 3, 4, 5, 6, and 7 mM, respectively. PA treated MCF-7 cells showed up-regulation of p53, Bax, caspase-3 and -9, and down-regulation of Bcl-2 gene (p â‰¤0.03). At IC50 (3.4 mM) of PA, the p53, Bax, caspase 3 and -9 genes were up-regulated by 6.34, 4.90, 23.45 and 15.03 folds respectively. Also, the fragmented genomic DNA in PA treated cells showed the signs of apoptosis. Our study endorsed the biological activity of PA and demonstrated the PA induced growth inhibition and apoptosis in MCF-7 cells by modulating the expression of apoptosis-regulatory genes. Â Keyword: Phytic acid, antioxidant, cytotoxicity, apoptosis, caspases, p53, Bax, Bcl-2, DNA fragmentation